Acute and sub-acute antihypertensive effects of syzygium polyanthum leaf extracts with determination of gallic a using HPLC analysis - Ismail, Azlini; Ramli, Nurul Syahida; Mohamed, Mahaneem; Wan Ahmad, Wan Amir Nizam (Phcog.net, 2018)
Context: Aqueous decoction of Syzygium polyanthum (ADSP) leaf is one of Malay traditionalremedial- preparations for hypertension. Intravenous ADSP reduced blood pressure of anesthetized Wistar-Kyoto (WKY) and Spontaneously-Hypertensive rats (SHR); however, acute and sub-acute effects of oral ADSP on conscious rats and its bioactive compound(s) are not comprehensively studied. This study aims to examine the acute and sub-acute effects of ADSP in comparison to methanol extract (MESP) on systolic blood pressure (SBP) of conscious WKY and SHR rats, as well as to identify their major phenolic-compound using highperformance- liquid-chromatography (HPLC). Methodology: For acute study, SHR and WKY rats were gavaged with single-dose of ADSP or MESP (2.00, 2.50 or 3.00 g/kg), vehicles, or losartan (0.01 g/kg). SBP was measured after 1, 3, 5, 6 and 24 hr-post-administration. For subacute experiment, SHR rats were gavaged once-daily with ADSP or MESP (2.50 g/kg/day), vehicles, or losartan (0.01 g/kg/day) for 3-week and their SBP was weekly-measured. Phenolic compounds were screened using ferric-chloride test, then gallic acid was determined using HPLC. Results: Acute administration of ADSP (2.50 to 3.00 g/kg) and MESP (2.00 to 3.00 g/ kg) significantly reduced SBP of SHR, but not of WKY rats. Repeated-daily-dose administration of MESP (2.5 g/kg/day) significantly reduced SBP of SHR after 2-week and sustained until 3-week, while ADSP (2.5 g/kg/day) significantly reduced SBP only after 3-week. Gallic acid was the major phenolic-compound in ADSP (157.09 ± 4.18 ppm) and MESP (134.04 ± 10.30 ppm). Conclusion: Oral ADSP and MESP that contain gallic acid possess acute and sub-acute antihypertensive effects in SHR, but MESP’s effect was more prominent than ADSP.